2018
DOI: 10.3390/e20060393
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Compression-Based Measures with Application to the Evolution of Primate Genomes

Abstract: An efficient DNA compressor furnishes an approximation to measure and compare information quantities present in, between and across DNA sequences, regardless of the characteristics of the sources. In this paper, we compare directly two information measures, the Normalized Compression Distance (NCD) and the Normalized Relative Compression (NRC). These measures answer different questions; the NCD measures how similar both strings are (in terms of information content) and the NRC (which, in general, is nonsymmetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 160 publications
0
5
0
1
Order By: Relevance
“…More concretely, they use relative entropy estimation between pairs of sequences of symbols, and then use classical classifiers (e.g., support vector machines) for text classification. Other applications of compression-based measures have been demonstrated by Pratas and colleagues, for genome analysis [ 17 , 18 ] or Carvalho et al for electro-cardiogram classification [ 19 ].…”
Section: Previous Workmentioning
confidence: 99%
See 2 more Smart Citations
“…More concretely, they use relative entropy estimation between pairs of sequences of symbols, and then use classical classifiers (e.g., support vector machines) for text classification. Other applications of compression-based measures have been demonstrated by Pratas and colleagues, for genome analysis [ 17 , 18 ] or Carvalho et al for electro-cardiogram classification [ 19 ].…”
Section: Previous Workmentioning
confidence: 99%
“…NRC has been used for applications such as authorship attribution [ 10 ], or studying the evolution of primate genomes [ 17 ]. The main advantage of NCD over NRC is that it can be evaluated using a common compressor, while the NRC requires a special-purpose one that is able to perform conditional compression.…”
Section: Similarity Measurement Using Nrcmentioning
confidence: 99%
See 1 more Smart Citation
“…Salah satu metode kompresi yang memiliki rasio kompresi yang cukup baik dan banyak digunakan saat ini adalah metode LZW. Metode LZW telah banyak digunakan pada beberapa penelitian perbandingan kompresi [4]- [11], [13], [16]. Sebagian hasil penelitian perbandingan menunjukkan LZW memiliki hasil rasio kompresi yang cukup baik sehingga pada penelitian ini juga akan digunakan sebagai pembanding terhadap metode kompresi differensiasi ASCII.…”
Section: Latar Belakangunclassified
“…Should we also measure the information needed to describe the model selection? Recently, we answered these questions [ 39 ] using the Normalized Relative Compression (NRC) [ 41 , 42 ]. In fact, we showed that, if the models are not qualified to handle a specific region, then the information required to measure similarity is transferred to the selection of the used model.…”
Section: Introductionmentioning
confidence: 99%